Preoperative percutaneous injection of methyl methacrylate and N-butyl cyanoacrylate in vertebral hemangiomas. - Cotten, A; Deramond, H; Cortet, B; Lejeune, J P; Leclerc, X; Chastanet, P; Clarisse, J (American Journal of Neuroradiology, 1996)
PURPOSE To investigate the usefulness of preoperative percutaneous injections in vertebral hemangiomas.METHODS Four patients presented with complicated vertebral hemangioma (spinal cord compression in three cases, intermittent spinal claudiction in one case). A three-part treatment was performed: initially, arterial embolization in three cases; 1 day later, percutaneous injections of methyl methacrylate into the vertebral body to strengthen it and of N-butyl cyanoacrylate into the posterior arch to optimize hemostasis during surgery; finally, the day after percutaneous injections, decompressive laminectomy and epidural hemangioma excision (when present).RESULTS Laminectomy was performed with minimal blood loss. The epidural component present in three cases was excised without any difficulty. The follow-up (average, 20 months) showed no evidence of vertebral collapse.CONCLUSION Percutaneous injections of methyl methacrylate and N-butyl cyanoacrylate might be useful before surgery for vertebral hemangiomas.